Cold periods and coronary events: an analysis of populations worldwide. Issue 7 (17th June 2005) - Barnett, Adrian G; Dobson, Annette J; McElduff, Patrick; Salomaa, Veikko; Kuulasmaa, Kari; Sans, Susana
Abstract : Study objective: To investigate the association between cold periods and coronary events, and the extent to which climate, sex, age, and previous cardiac history increase risk during cold weather. Design: A hierarchical analyses of populations from the World Health Organisation's MONICA project. Setting: Twenty four populations from the WHO's MONICA project, a 21 country register made between 1980 and 1995. Patients: People aged 35–64 years who had a coronary event. Main results: Daily rates of coronary events were correlated with the average temperature over the current and previous three days. In cold periods, coronary event rates increased more in populations living in warm climates than in populations living in cold climates, where the increases were slight. The increase was greater in women than in men, especially in warm climates. On average, the odds for women having an event in the cold periods were 1.07 higher than the odds for men (95% posterior interval: 1.03 to 1.11). The effects of cold periods were similar in those with and without a history of a previous myocardial infarction. Conclusions: Rates of coronary events increased during comparatively cold periods, especially in warm climates. The smaller increases in colder climates suggest that some events in warmer climates are preventable. It is suggested that people living in warm climates, particularly women, should keep warm on cold days.